THE EFFECT OF A PROBLEM-BASED LEARNING MODEL ON STUDENTS' CRITICAL THINKING SKILLS IN PHYSICAL FITNESS GYMNASTICS MATERIAL AT SMP NEGERI 1 LAWE SIGALA-GALA - Hendra Putra; Fakhrur Rizal; Afrizal (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aimed to determine the effect of the Problem-Based Learning (PBL) model on students' critical thinking skills within the context of Physical Fitness Gymnastics, a component of Physical Education (PE). Employing a quasi-experimental design with a one-group pretest-posttest approach, the research was conducted with 30 eighth-grade students from SMP Negeri 1 Lawe Sigala-Gala, selected via total sampling. The intervention consisted of a series of lessons on the "Indonesian Fantastic Children's Gymnastics" (Senam Anak Indonesia Hebat) delivered using the PBL model, where students worked collaboratively to solve authentic problems related to gymnastic sequences, techniques, and health benefits. Critical thinking skills, operationalized through five indicators—analysis, reasoning, evaluation, reflection, and decision-making—were measured using a validated essay test. The results indicated a substantial increase in the mean score from 48.7 in the pretest to 76.7 in the posttest. A paired-sample t-test revealed a statistically significant difference between the pretest and posttest scores (t (29) = 15.87, p < 0.05), with the t-value exceeding the critical t-table value of 2.04. This leads to the conclusion that the implementation of the Problem-Based Learning model has a significant positive effect on enhancing students' critical thinking skills in the subject of physical fitness gymnastics. The findings advocate for the integration of PBL as an effective pedagogical strategy in the PE curriculum to foster higher-order thinking skills alongside physical proficiency.